Human D-Amino Acid Oxidase: Structure, Function, and Regulation - Pollegioni, Loredano; Sacchi, Silvia; Murtas, Giulia (Frontiers in Molecular Biosciences, 2018)
D-amino acid oxidase (DAAO) is an FAD-containing flavoenzyme that catalyzes with absolute stereoselectivity the oxidative deamination of all natural D-amino acids, the only exception being the acidic ones. This flavoenzyme plays different roles during evolution and in different tissues in humans. Its three-dimensional structure is well conserved during evolution: minute changes are responsible for the functional differences between enzymes from microorganism sources and those from humans. In recent years several investigations focused on human DAAO, mainly because of its role in degrading the neuromodulator D-serine in brain astrocytes. D-Serine is the main coagonist of N-methyl D-aspartate receptors, i.e., excitatory amino acid receptors critically involved in main brain functions and pathologic conditions. Human DAAO possesses a weak interaction with the FAD cofactor; thus, in vivo it should be largely present in the inactive, apoprotein form. Binding of active-site ligands and the substrate stabilizes flavin binding, thus pushing the acquisition of catalytic competence. Interestingly, the kinetic efficiency of the enzyme on D-serine is very low. Human DAAO interacts with various proteins, in this way modulating its activity, targeting, and cell stability. The known properties of human DAAO suggest that its activity must be finely tuned to fulfill a main physiological function such as the control of D-serine levels in the brain. At present, studies are focusing on the epigenetic modulation of human DAAO expression and the role of post-translational modifications on its main biochemical properties at the cellular level.